Pengaruh Pemanfaatan Quizizz dan Penggunaan Fasilitas Belajar terhadap Hasil Belajar Mahasiswa Pendidikan Administrasi Perkantoran Universitas Negeri Jakarta - Apriliana Dian Fadillah; Marsofiyati Marsofiyati (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines the impact of utilizing Quizizz and learning facilities on the academic performance of students majoring in Office Administration Education at the State University of Jakarta. The study uses a quantitative approach with a descriptive method. The population consists of all students in the Faculty of Economics at the State University of Jakarta. A purposive sampling technique was used to select a sample of 40 students from the Office Administration Education Study Program, class of 2022, at the State University of Jakarta. Data was gathered through a questionnaire utilizing a 4-point Likert scale and analyzed using descriptive statistical techniques, validity tests, reliability tests, and hypothesis testing. The results of the study indicate that the use of Quizizz and learning facilities have a positive and significant effect on student learning outcomes.